Cross-Jurisdictional Reporting Standards for Cash Waqf: A Comparative Normative Legal Study of Indonesia and Malaysia - Bagas Heradhyaksa; Nur Khoirin; Mustla Sofyan Tasfiq; Ahmad Wahyudi; Islamiyati; Wawaysadhya (El-Mashlahah, 2026)
Cash waqf holds real promise for Islamic social finance. Its potential, however, has not been matched by equally reliable governance. This study fills that gap by conducting a comparative normative analysis of reporting obligations and transparency standards in cash waqf governance across Indonesia and Malaysia. It proposes a cross-jurisdictional minimum standard that can serve both institutional models without displacing either. This study adopts a doctrinal (normative) legal approach with a comparative method, analysing Indonesia’s legal instruments and the enactments of Malaysian states, as well as the concepts of accountability, transparency, and good governance. The findings show that while both countries recognize reporting as a governance instrument to ensure accountability, there are differences in institutional design and standardization. Indonesia applies an integrated system with reporting obligations from nazhir and LKS-PWU, but there is a risk of fragmentation without standardized publication formats. In contrast, Malaysia employs a state-based system, where SIRC/MAIN centralizes reporting obligations, but variations across states could reduce comparability and uniform minimum disclosure. This normative contribution advances the discourse on Islamic waqf governance by offering an actionable minimum standard that bridges two divergent institutional models, centralized national regimes and decentralized state-based systems, thereby filling a critical gap in cross-jurisdictional waqf governance scholarship.